Prevalence of Risky Sexual Behaviours among Young Adults attending Urban Universities in Uganda - Winfred Biribonwa Kyosaba; David Kani Olema; Aloysius Rukundo (East African Journal of Education Studies, 2025)
Risky sexual behaviours (RSBs) among young adults are a worry in Ugandan Universities. These are actions that heighten the likelihood of acquiring Human immunodeficiency virus (HIV), other Sexually Transmitted Infections (STIs), and unintended pregnancies among young adults. This study examined the prevalence and forms of RSBs among young adults in Ugandan universities. The research targeted students aged 18–25 years from 4 universities in Kampala. A mixed methods concurrent design was employed, involving 527 randomly selected students. Quantitative data were collected using a structured self-administered questionnaire, while qualitative insights were obtained through focus group discussions with peers and student leaders. Quantitative data were analysed using SPSS Version 23 to generate frequencies and percentages, whereas qualitative data were interpreted using Interpretative Phenomenological Analysis. Findings indicated that 346(65.7%) students had previously engaged in sexual activity, and 330(62.6%) were sexually active at the time of the study period. Male students were more likely to engage in RSBs 185(74.0%) compared to females 16(58.1%). With over 60% of participants actively involved in RSBs, the prevalence highlights significant exposure to STIs, including HIV, and unintended pregnancies. The study concluded that RSBs were highly prevalent among young adults in Ugandan universities. The study recommends urgent targeted interventions, including comprehensive peer-led sexual and reproductive health education and the establishment of youth-friendly health services like contraceptive clinics. These measures would empower students with the knowledge, skills and resources to reduce RSBs and improve their sexual health outcomes.
Keywords: Risky Sexual Behaviours; Young Adults; Human Immunodeficiency Virus; Sexually Transmitted Infections; and Interventions